การดูดซับไฮโดรเจนซัลไฟด์ในแก๊สชีวภาพโดยใช้ซิลิกาดัดแปร - แววดาว ใจบุญ (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
The high porous adsorbent, silica xerogel modified by addition of amine groups, Triamine and Polyethyleneimine (Mw 800, 2000 and 25000), was prepared for H₂S adsorption. The effect of variables, adsorbent type, amount of amine loading, operating temperature, and gas flow rate on H₂S adsorption were investigate. The adsorption of the amine groups enhanced hydrogen sulfide removal efficiency and the adsorbent has a good selectivity of acid gases. The sorbent was characterized by Thermo Gravimetic Analysis (TGA), Fourier Transform Infrared Spectroscopy (FTIR), Brunauer Emmett Teller (BET), X-ray diffractometer (XRD) and Scanning Electron Microscope (SEM). The results showed that Si-PEI800-50 gave good breakthrough and saturation capacity of 0.449 and 0.629 mmol/g-sorb, respectively. This result indicated that the sorbents are promising for removing hydrogen sulfide. Moreover, the sorption-desorption loops showed that the Si-PEI800-50 had good regenerability and stable sorption performance.